Se déplacer avec des enfants à Bruxelles ? - Bertrand Montulet; Michel Hubert (Brussels Studies, 2008)
By means of a typology of “attitudes towards space and time”, the authors evaluate the suitability of various modes of transport in terms of the limitations of people who live with children under the age of twelve and who travel on a daily basis in Brussels. The study underlines the shortcomings of public transport, in particular regarding those for whom time management is especially important (for themselves or for the well-being of the children who accompany them). In order to meet the needs of a public who are often stressed, in a hurry and worried, the authors suggest that the transport service must be humanised in order to make life easier for users, rather than expecting them to acquire more and more technical skills to make use of the tangled networks and adapt to the offer. In this respect, improvements in the comfort, equipment and accessibility at stops and points of modal and intermodal change are particularly important and all too rare in Brussels. More generally, the authors assess the attractiveness of public transport by considering the different stages of life of users and the many ways they organise their daily activities. They also insist on the contribution which public transport may make to the necessary synchronisation of urban temporalities.